A prediction model for aircraft landing–induced bridge impact coefficients based on bayesian optimization and gradient boosting algorithms - Hui Jiang; Yixuan Li; Junjun Guo; Xianfeng Meng; Guangsong Song; Boqian You (Engineering Structures, 2026)

Enriching triboelectric signal characteristic toward vibration waveform recognition by electron-beam irradiation - Hu Bian; Fanzheng Zeng; Haoran Yu; Xingyi Song; Jia Liu; Xingke Zhao; Zhenming Chen; Chengmei Gui; Junjun Huang (Chemical Engineering Journal, 2026)

Probabilistic assessment of post-earthquake running safety threshold for high-speed railway bridge based on nonparametric copula method - Yan Zhang; Guangsong Song; Hui Jiang; Junjun Guo; Qikai Sun; Yun Shan (Soil Dynamics and Earthquake Engineering, 2026)

Profiling the spatial heterogeneity of microbiomes and volatilomes along internal environmental gradients in high-temperature Daqu - Guangdong Gan; Junjun He; Yong Yang; Lulu Song; Chun Pu; Chunlin Zhang (Food Bioscience, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Coupled tectonic-climatic-oceanographic dynamics drove the evolution of foraminiferal diversity in South China during the Middle to Late Mississippian - Chao Liu; Junjun Qi; Pedro Cózar; Ismael Coronado; Fei Li; Weiqing Liu; Meng Li; Ping Wang; Xin Li; Xia Hu; Song Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Exploring diverse physical technologies for microbial inactivation and toxin degradation in rice: A comprehensive review - Bengang Wu; Chenyu Song; Yiting Guo; Lei Cong; Junjun Dai; Shenao Nan; Yan Shen; Haile Ma (Food Control, 2026)

On field measurement for absorption properties of biomass burning aerosols in the North China Plain and climate implications - Yang Wang; Yansong Xu; Ruonan Bian; Junjun Deng; Yichen Ma; Song Guo; Jing Wang (Science China Earth Sciences, 2026)

Enhancing drying behavior and textural properties of carrot slices by infrared drying combining contact ultrasound - Bengang Wu; Chenyu Song; Yiting Guo; Kun Gao; Ningning Ouyang; Shenao Nan; Junjun Dai; Yan Shen; Haile Ma (Food and Bioproducts Processing, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

A Middle Devonian fluvial-delta plain complex from eastern Yunnan, South China: Insights into co-evolution between environments and organisms in an early non-marine system - Junjun Song; Xiaole Zhang; Sha Li; Wenkun Qie; Yi Wang; Honghe Xu (Earth-Science Reviews, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Supramolecular self-assembling IGF-1 nanofibers modulate neutrophil extracellular traps to accelerate diabetic wound healing - Xuebo Wei; Tengfei Qi; Qizhi Shuai; Ying Zhang; Yun Xu; RuiYang Sun; ZhuoYang Song; Junjun Luo; Yinnan Zhang; Hongyu Zhang; Chunqiu Zhang; Jie Gao; et al. (Chemical Engineering Journal, 2025)

Hydroxysafflower yellow A alleviates the inflammatory response in astrocytes following cerebral ischemia by inhibiting the LCN2/STAT3 feedback loop - Lijuan Song; Yige Wu; Lijun Yin; Yanzhe Duan; Jianlin Hua; Mengwei Rong; Kexin Liu; Junjun Yin; Dong Ma; Ce Zhang; Baoguo Xiao; Cungen Ma (Metabolic Brain Disease, 2025)

Astronomically forced dynamics of Late Devonian (Famennian) sea level and biotic recovery in western Junggar, Northwest China - Kunyuan Ma; Linda Hinnov; Zhihong Wang; Kai Wang; Ruiwen Zong; Xinsong Zhang; Junjun Song; Yang Bai; Yiming Gong (Global and Planetary Change, 2025)

Periodically asymmetric responses of deep chlorophyll maximum to light and thermocline in a clear monomictic lake: Insights from monthly and diel scale observations - Jingyi Li; Qichao Zhou; Yue Dao; Di Song; Zhirong Yu; Junjun Chang; Erik Jeppesen (Science of The Total Environment, 2024)

Macrophage migration inhibitory factor reversed senescent phenotype in human chondrocytes in vitro - Zhenlan Fu; Qingqing Li; Peiyao Jiang; Xiongbo Song; Junjun Yang; Guangxing Chen; Xiaoyuan Gong; Liu Yang (Molecular Biology Reports, 2024)

Evaluation of biological activity and prebiotic properties of proanthocyanidins with different degrees of polymerization through simulated digestion and in vitro fermentation by human fecal microbiota - Xiaoyi Chen; Shuai Liu; Hong Song; Chunlong Yuan; Junjun Li (Food Chemistry, 2024)

Preparation of active film based on cinnamon essential oil into β-cyclodextrin with high hydrophobic and its preservation for griskin - Yefeng Guan; Junjun Zhang; Jianing Zhang; Wenjun Song; Jiyong Shi; Xiaowei Huang; Xiaodong Zhai; Di Zhang; Zhihua Li; Xiaobo Zou (Food Control, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

A ratiometric fluorescence amine sensor based on carbon quantum dot-loaded electrospun polyvinylidene fluoride film for visual monitoring of food freshness - Wenjun Song; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Yuhong Xue; Yue Sun; Wei Sun; Junjun Zhang; Xiaowei Huang; Zhihua Li; Tingting Shen; Yanxiao Li; et al. (Food Chemistry, 2024)

cTBS to Right DLPFC Modulates Physiological Correlates of Conflict Processing: Evidence from a Stroop task - Ping Xu; Song Wang; Yulu Yang; Bishal Guragai; Qiuzhu Zhang; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Topography, 2024)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Application of phosphorus amendments reduces metal uptake and increases yield of Oryza saliva L. (rice) in Cd/Cu-contaminated paddy field - Jiahui Wu; Qingmei Song; Yingxin Wu; Junjun Liu; Zhuohao Wu; Jingyan Zhou; Yuntao Wang; Wencheng Wu (Chemosphere, 2023)

Influence of MnO2 crystal existing form on its catalytic performance for toluene oxidation - Xuxu Zhai; Luming Li; Shuang Song; Junjun Zhang; Jun Ma; Chongrui Xie; Wei Chu (Fuel, 2023)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Hybrid Scheduling for Multi-Equipment at U-Shape Trafficked Automated Terminal Based on Chaos Particle Swarm Optimization - Junjun Li; Jingyu Yang; Bowei Xu; Yongsheng Yang; Furong Wen; Haitao Song (Journal of Marine Science and Engineering, 2021)
Aimed to improve the efficiency of port operations, Shanghai Zhenhua Heavy Industries Co., Ltd. (ZPMC) proposed a new U-shape trafficked automated terminal. The new U-shape trafficked automated terminal brings a new hybrid scheduling problem. A hybrid scheduling model for yard crane (YC), AGV and ET in the U-shape trafficked automated terminal yard is established to solve the problem. The AGV and ET yard lanes are assumed to be one-way lane. Take the YC, AGV and ET scheduling results (the container transportation sequences) as variables and the minimization of the maximum completion time as the objective function. A scheduling model architecture with hierarchical abstraction of scheduling objects is proposed to refine the problem. The total completion time is solved based on a static and dynamic mixed scheduling strategy. A chaotic particle swarm optimization algorithm with speed control (CCPSO) is proposed, which include a chaotic particle strategy, a particle iterative speed control strategy, and a particle mapping space for hybrid scheduling. The presented model and algorithm were applied to experiments with different numbers of containers and AGVs. The parameters of simulation part refer to Qinzhou Port. The simulation results show that CCPSO can obtain a near-optimal solution in a shorter time and find a better solution when the solution time is sufficient, comparing with the traditional particle swarm optimization algorithm, the adaptive particle swarm optimization algorithm and the random position particle swarm optimization algorithm.

Devonian-Carboniferous boundary in China - Wenkun Qie; Yuanlin Sun; Wen Guo; Ting Nie; Bo Chen; Junjun Song; Kun Liang; Baoan Yin; Shupeng Han; Junying Chang; Xiangdong Wang (Palaeobiodiversity and Palaeoenvironments, 2021)

Ostracods from the Devonian-Carboniferous transition in Dushan of Guizhou, South China - Junjun Song; Yiming Gong (Palaeobiodiversity and Palaeoenvironments, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Mapping soil organic carbon stocks of northeastern China using expert knowledge and GIS-based methods - Xiaodong Song; Feng Liu; Bing Ju; Junjun Zhi; Decheng Li; Yuguo Zhao; Ganlin Zhang (Chinese Geographical Science, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

A 796 bp PsPR10 gene promoter fragment increased root-specific expression of the GUS reporter gene under the abiotic stresses and signal molecules in tobacco - Xiangbin Xu; Sai Guo; Kai Chen; Hongmiao Song; Junjun Liu; Longbiao Guo; Qian Qian; Huizhong Wang (Biotechnology Letters, 2010)